2016
DOI: 10.1097/rli.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion Magnetic Resonance Imaging in Partially Nephrectomized Kidneys

Abstract: Our study suggests that quantitative parameters derived from DWI are highly indicative of renal function. Apparent diffusion coefficients showed substantial differences in the renal cortex after PN, whereas an IVIM analysis delivered additional insight into kidney physiology. Quantitative DWI, particularly perfusion-related IVIM parameters, therefore demonstrated great potential as truly noninvasive biomarker to obtain information about single kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…DWI is a powerful MRI technique used for imaging molecular movement or diffusion that reflects changes in microstructure of biological tissues . Previous studies have confirmed that IVIM‐DWI can be used to assess renal function . However, renal pathology plays an important role in guiding therapy and follow‐up of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…DWI is a powerful MRI technique used for imaging molecular movement or diffusion that reflects changes in microstructure of biological tissues . Previous studies have confirmed that IVIM‐DWI can be used to assess renal function . However, renal pathology plays an important role in guiding therapy and follow‐up of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that IVIM parameters were sensitive to chronic renal impairment, such as the grade of clear cell renal cell carcinoma, diabetic kidney, ureteral obstruction and renal artery stenosis . The decrease in renal cortical perfusion can explain the alteration in magnetic resonance parameters when renal function changes . Therefore, we presumed that diffusion MRI, which is able to characterize renal microstructure and microcirculation, can potentially detect acute changes in renal function after exposure to high‐pressure renal pelvic perfusion.…”
Section: Introductionmentioning
confidence: 64%
“…Our analysis of kidneys both contralateral and ipsilateral to renal lesions suggests functional compromise, perhaps reflecting a general deficit that patients have in comparison to controls. Renal ADC has previously been shown to be decreased in the ipsilateral kidney postpartial nephrectomy, as well as in renal artery stenosis and renal failure …”
Section: Discussionmentioning
confidence: 97%